TECHNOLOGY EMPOWERED STUDENTS â€œPREPARE YOURSELF FOR INTERCONNECTED WORLDâ€ - Gumawang, Gumawang (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Rapid development of digital technology has changed the skills required in the job. Universities are, without question, making attempts to change in facing the challenges in the era of industrial revolution 4.0. In the first part of this paper, the rapid changing of the technology, highlighting the rapid change in industry and education, is discussed along with the exponential growth of innovations. The Presence of Artificial Intelligence that has changed jobs and skills required in the industries and other areas are addressed in the second part. The last section of this paper, some tips on how to face the rapid changes of technology and how to continue learning beyond the classroom wall are discussed.